Arab associations in Valparaiso during the twentieth century. A mechanism of integration into the host society - Estrada, Baldomero (Cuadernos de Historia, 2016)
The paper attempts to show, as the ethnic associations structure of the Arab community of Valparaiso helps in the process of integration into the host society. It assumes the existence of two positions on the matter. On the one hand, it is argued that associations facilitate the integration of immigrants into the host society (integration theory) and on the other hand states that the institutions created by immigrants strengthen their identity and their slow integration (enclave theory). A historical view of the subject considering aspects such as international positioning of the country of origin of communities, socio-economic developments, future prospects and number of members is suggested. It is perceived to institutions as a result of the aforementioned features and no such causal relationship established with the host society.